Social and Emotional Drivers of Engagement with AI Virtual Influencers: A Qualitative Study in Indonesia - Kembau, Agung Stefanus; Bernanda, Devi Yurisca; Kumaat, Arief Perdana; Lendo, Fresi Breatrix; Doa, Fidelia Novena (Universitas Pelita Harapan, 2025)
The growing presence of AI-powered virtual influencers (VIs) on social media has introduced new dynamics in digital marketing, yet little is known about how consumers in emerging markets perceive and respond to these synthetic personas. This study investigates the factors that shape consumer acceptance of virtual influencers in Indonesia, focusing on the interrelationship between social influence, performance expectancy, emotional resonance, and willingness to engage. Employing a qualitative research design, 25 in-depth semi-structured interviews with Indonesian consumers aged 18–35 were conducted, reaching thematic saturation. Thematic analysis was conducted using NVivo 14, integrating both deductive and inductive coding strategies. Findings reveal four major themes and twelve subthemes: (1) social influence functions as a cultural endorsement mechanism, shaping normative beliefs; (2) performance expectancy is driven by informational credibility, entertainment value, and behavioral consistency; (3) emotional resonance—expressed through perceived authenticity and psychological comfort—is central to consumer attachment; and (4) willingness to use VIs is closely linked to digital identity projection and contextual social legitimacy. A clear majority of participants (around four out of five) described positive evaluations of VIs, while a minority expressed skepticism and emotional discomfort, highlighting ethical and psychological boundaries in AI–human interaction. The study contributes to a deeper understanding of how social and emotional mechanisms converge in shaping digital consumer behavior, offering practical insights for marketers and advancing theory on technology acceptance in culturally nuanced settings.